(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
Research results show that nitrogen losses in the form of nitrates are particularly high in irrigated fields and depend significantly on the soil texture and the rate and timing of irrigation. The nitrogen, phosphorus, and potassium content of the soil fluctuate during the growing season.